2014
DOI: 10.1007/s12928-014-0253-9
|View full text |Cite
|
Sign up to set email alerts
|

Short- and mid-term results of balloon angioplasty for renal artery fibromuscular dysplasia

Abstract: This study aimed to evaluate short- and mid-term outcomes of percutaneous transluminal renal artery angioplasty (PTRA) in patients with symptomatic renal artery stenosis caused by renal artery fibromuscular dysplasia (RAFMD). Retrospective analysis of 22 patients with RAFMD who were performed PTRA between 2006 and 2012. These patients underwent PTRA due to poorly controlled hypertension. Pre- and post-PTRA blood pressure (BP) measurements and renal function were evaluated. Freedom from events (restenosis, repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…Restenosis after PTA is a key factor affecting blood pressure outcomes. According to the literature, the incidence of restenosis is 15–35% . However, studies indicate that most patients benefit from secondary PTA treatment and this study showed similar results.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Restenosis after PTA is a key factor affecting blood pressure outcomes. According to the literature, the incidence of restenosis is 15–35% . However, studies indicate that most patients benefit from secondary PTA treatment and this study showed similar results.…”
Section: Discussionsupporting
confidence: 77%
“…According to the literature, the incidence of restenosis is 15-35%. 15,17,18 However, studies indicate that most patients benefit from secondary PTA treatment and this study showed similar results. Previous literature reported renal artery in-stent stenosis is 10% in patients with atherosclerotic RAS, 19 but the restenosis rate of selective stent is very low in this study.…”
Section: Renal Artery Restenosissupporting
confidence: 78%
“…The only data available are derived from observational studies showing clinical benefit with interventional therapy. Periprocedural adverse effects that often complicate interventions in ARAS are rare in FMD, thus making patients with FMD more eligible for intervention . In cases where FMD involves distal or smaller branches, percutaneous intervention becomes difficult and restenosis is more common …”
Section: Managementmentioning
confidence: 99%
“…Even though there are no studies comparing endarterectomy with percutaneous interventions, and given that FMD is not focal but diffuse and sometimes bilateral, it seems that endarterectomy is not the first‐line therapy for these patients. Furthermore, since percutaneous interventions are quite effective not only in BP control but also in preserving renal function, endarterectomy should be reserved solely for patients who cannot be treated otherwise …”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation